Leukocyte Adhesion Deficiency-I variant Syndrome (LAD-Iv, LAD-III): Molecular Characterization of the Defect in an Index Family - Harris, ES (2011)
Leukocyte adhesion deficiencies are rare clinical syndromes of impaired host defense that provide novel insights into regulation of immune and inflammatory responses (1,2). Leukocyte adhesion deficiency (LAD)-I variant (LAD-Iv), also called LAD-III, is a unique disorder in which inside-out signaling of β(1), β(2), and β(3) integrins on leukocytes and platelets is disrupted, leading to impaired cellular adhesion, recurrent infections, and bleeding [1-3]. We originally reported the second patient with this disorder to be identified and characterized the adhesive deficiencies and functional phenotype of this subject's leukocytes [4]. Here we show that the molecular defect in this index subject is a new mutation in FERMT3 (KINDLIN-3) which encodes KINDLIN-3, a cytoskeletal protein that interacts with the cytoplasmic tails of β(1), β(2), and β(3) integrins and is required for inside-out and outside-in signaling of these heterodimers [5, 6]. We also report clinical features and previously-unrecognized defects in cells from a new patient, a sibling of the original subject that we described who carries the same FERMT3 mutation. Mutations in FERMT3 have now been shown to be the basis for LAD-Iv/LAD-III in each of the four original patients or families that established this syndrome[4, 7-9], including the family that we describe.